Effect of fires on vegetation cover, carbon storage and plant biomass in a coastal wetland: The case of Los Pantanos de Villa (Lima-Peru), a wetland on the arid Pacific coast - Ramirez, Dámaso W. (2022)
Introduction: Wetlands are among the most productive ecosystems, but currently are being degraded or eliminated at accelerated rates by multiple anthropic activities. In the central coast of Peru, wetlands suffer recurring fires, and the little-studied effects include the level of emissions and carbon sequestration by burning. Objective: To estimate carbon in aerial biomass affected by fire, and carbon recovered by the vegetation after one year. Methods: We worked in Los Pantanos de Villa (Lima, Peru) coastal wetland and compared burnt (32 quadrants, 1 m2) and unaffected areas (33 quadrants). Results: The vegetation affected was predominantly herbaceous and dominated by Phragmites australis, Schoenoplectus americanus, Typha dominguensis and Cladium jamaicense. Fire affected 1 147.0 t of plant biomass that stored 381.8 t of carbon, generating the emission of 1 397.1 t of CO2 into the atmosphere. After one year, 79 % of the vegetation cover had recovered, but only 26 % of the plant biomass and 12.8 % of vegetation carbon. Conclusions: Appropriate indicators of wetland fire resilience should consider that fire-impacted wetland rapidly recovers plant cover, but not carbon storage and plant biomass.